Impact of preoperative extracorporeal life support on left ventricular assist device outcomes: A comparative study. Issue 7 (July 2019) - Zhigalov, Konstantin; Szczechowicz, Marcin; Mashhour, Ahmed; Mkalaluh, Sabreen; Safonov, Dmitrii; Enginoev, Soslan; Easo, Jerry; Ennker, Juergen; Eichstaedt, Harald C; Weymann, Alexander
Background: To investigate whether preoperative short-term extracorporeal life support therapy in patients undergoing continuous-flow left ventricular assist device implantation has an impact on the outcome regarding survival and adverse events. Methods: Between January 2011 and May 2018, 100 consecutive patients received HeartMate II, HeartWare, or HeartMate III for end-stage heart failure. Mean age was 64.2 ± 10.3 years. Three patient groups were identified: without preoperative extracorporeal life support (non-extracorporeal life support group, n = 80), with preoperative extracorporeal life support due to postcardiotomy shock after conventional cardiac surgery (postcardiotomy shock group, n = 9), and with preoperative extracorporeal life support without previous surgery (non-postcardiotomy shock group, n = 11). The primary endpoint was overall survival after device implantation. Secondary endpoints were adverse events during the follow-up period. Results: Survival was significantly different between the groups (p < 0.05): 30-day, 6-month, and 1-year survival rates were 85%, 68%, and 61% for non-extracorporeal life support group; 44%, 22%, and 22% for postcardiotomy shock group; and 45%, 27%, and 24% for non-postcardiotomy shock group, respectively. Furthermore, in both extracorporeal life support groups (postcardiotomy shock and non-postcardiotomy shock), there were a higher incidence (p < 0.05) of postoperative right heart failure (30% vs 66.7% vs 54.5%), acute renal failure requiring dialysis (20% vs 77.8% vs 54.5%), and respiratory failure (31.3% vs 88.9% vs 81.8%). Conclusion: Continuous-flow left ventricular assist device implantation with prior extracorporeal life support appears to have a worse outcome regarding survival, right heart failure, renal and respiratory dysfunction (p < 0.05). Future studies have to be done to evaluate the outcome after extracorporeal life support bridge pre-left ventricular assist device, especially as ultima ratio in postcardiotomy shock patients.